Comparative Analysis of Lateral Preferences in Patients With Resistant Schizophrenia - Panov, Georgi (Frontiers in Psychiatry, 2022)
Schizophrenia is a mental illness in which a significant percentage of patients remain resistant to therapeutic interventions. Numerous studies have been conducted to analyze functional lateralization in patients with schizophrenia with mixed results. We conducted a comparative study evaluating the lateralization of the hand, foot and eye in patients with resistance to treatment and those in remission. We found a significant predominance of patients with cross-dominance as well as left-sided dominance of the eye in the group of patients with resistance to therapy.